Urgensi Perceraian Pernikahan Siri di Pengadilan Agama Stabat - Diyan Yusri; Satria Aridarma (Fakultas Syariah IAIN Laa Roiba Bogor, 2021)
This research is titled Urgency of Divorce of Siri Marriage in Stabat Religious Court (Case Study of Stabat Religious Court Case Number 583). The background of this title is the existence of a marriage of siri which is carried out by a man and woman, but when he wants to get a divorce the wife makes a divorce to the Stabat Religious Court. The main problem in this study is what is the urgency or encouragement of the wife to make a divorce suit to her husband in the Stabat Religious Court even though they only do a series of marriages. This research is a type of library research (library research) which is a case study. Data in the form of the decision of the Stabat Religious Court number 583 / Pdt.G / 2019 / PA.Stb, secondary data books relating to the title that supports the research. Data collection techniques documentation, interviews and literature study. Content analysis techniques. Based on the results of the study, it was found that the Stabat Religious Court accepting divorce lawsuits from Siri marriages is to avoid any harm and to gain goodness both legally and philosophically. The urgency of divorce carried out in the Religious Courts is in order to obtain legal certainty of divorce and to facilitate all administrative matters for children born from such marriages. And in essence the divorce suit from the marriage of siri which is granted is to avoid harm and gain benefit. Key wodrs: Perceraian, Nikah, Siri